Assessment of Infraorbital Hypesthesia Following Orbital Floor and Zygomaticomaxillary Complex Fractures Using a Novel Sensory Grading System. Issue 1 (January 2019) - Homer, Natalie; Glass, Lora R.; Lee, N. Grace; Lefebvre, Daniel R.; Sutula, Francis C.; Freitag, Suzanne K.; Yoon, Michael K.
Abstract : Purpose: : Introduction of a novel sensory grading system to assess the incidence and long-term recovery of infraorbital hypesthesia following orbital floor and inferior orbital rim fractures. Methods: : Patients who presented for evaluation of orbital floor and/or zygomaticomaxillary complex (ZMC) fractures between January 2015 and April 2016 were analyzed. Two-point subjective infraorbital sensory grading in 5 discrete anatomic areas was performed. Fractures were repaired based on traditional criteria; hypesthesia was not an indication for surgery. The sensory grading system was repeated a mean 21.7 months (range 18–28) after initial fracture. Results: : Sixty-two patients (mean 41.8 years) participated in the initial symptom grading, and 42 patients (67.7%) completed the 2-year follow-up. Overall, 20 of 42 patients (47.6%) had some infraorbital hypesthesia. There were fewer with isolated orbital floor fractures versus ZMC fractures (31.8% vs. 68.4%; p = 0.019). Two years postinjury, 9.1% and 40.0% with isolated floor and ZMC fractures, respectively, had persistent sensory disturbance ( p = 0.0188). Of patients with sensory disturbance on presentation, 71.4% with isolated floor fractures and 38.5% with ZMC fractures experienced complete sensory recovery ( p = 0.1596). Patients with isolated floor fractures had improved recovery after surgery (100% vs. 33.3% recovery; p = 0.0410). Patients with ZMC fractures showed no difference in sensory prognosis between those repaired and observed. Conclusions: : In this pilot study, isolated orbital floor fractures carried a good infraorbital sensory prognosis, further improved by surgical repair. Zygomaticomaxillary complex fractures portended a worse long-term sensory outcome, unaffected by management strategy. This study validates the novel sensory grading system in post-fracture analysis. Abstract : Assessment of the incidence and long-term recovery of infraorbital hypesthesia following orbital floor and inferior orbital rim fractures using a novel sensory grading system.